Cognitive flexibility in autism: Evidence from young autistic children. Issue 12 (4th October 2022) - Andreou, Maria; Konstantopoulos, Kostas; Peristeri, Eleni
Abstract: We examined the cognitive flexibility performance of young autistic children and a group of neurotypical peers. Thirty‐six autistic children (72–83 months) and 200 age‐matched typically‐developing children were assessed on the Children's Color Trails Test (CCTT), a semantic and a phonemic verbal fluency task. The results showed that the autistic children performed worse than their neurotypical peers in the switching component of the CCTT. In the fluency tests, the autistic group generated overall fewer word items than their neurotypical peers, however, their poorer performance was driven by specific linguistic stimuli in the fluency tasks. The findings suggest that cognitive flexibility for the autistic children was affected in the nonverbal CCTT only, while poor performance in semantic and phonemic fluency seemed to be inherent to the language properties of the verbal fluency tasks. Lay Summary: The current study aims to determine whether the Children's Color Trails Test (CCTT) and verbal (semantic and phonemic) fluency tasks are appropriate to assess cognitive flexibility in young autistic children. The overall findings showed poor performance for the autistic children in the CCTT. On the other hand, verbal fluency performance seemed to be driven by language features specific to the semantic and the phonemic fluency tasks rather than by difficulties in cognitive flexibility.